Dinamika identitas nasional di era globalisasi: kolaborasi pendidikan dan agama - Daroini, Muhammad Fauzi (Maliki Interdisciplinary Journal, 2026)
The wave of globalization presents existential challenges that risk eroding Indonesia's national identity through the dominance of foreign cultures, shifts in ideological orientation, and a digital landscape that triggers social polarization. Efforts to defend the nation's identity cannot rely solely on the supremacy of law; they require anticipatory measures through character education and the instillation of religious values from an early age. This study aims to examine the crucial role of integrative education and religious moderation in fortifying national identity, using the educational model at the State Islamic University (UIN) of Maulana Malik Ibrahim Malang as a reference. Employing a qualitative-descriptive method based on literature review, this research analyzes various literature on the impacts of globalization and its alternative solutions. The findings indicate that the transformation towards integrative education as materialized through the "Tree of Knowledge" curriculum metaphor, the creation of the Ulul Albab profile, and the integration of the Ma'had (dormitory) system with the campus has proven effective in safeguarding the rationality and spiritual depth of the younger generation from moral degradation. Furthermore, instilling religious moderation (Religious Nationalism) and actualizing Pancasila values position religion as the ethical foundation in nurturing plurality. In conclusion, solid collaboration among educational institutions, families, and the social environment is an absolute prerequisite for producing a future generation that is globally competitive yet firmly holds onto the local wisdom of the archipelago.